Health Education for Elderly to Prevent Obesity at the Yayasan Pondok Lansia Bahagia Surabaya - Vivera Pane, Rita; Aisyah; Handayani; Zaman Al Hajiri, Aufar Zimamuz; Isna Rahmawati, Rima (Journal of Health Community Service, 2024)
Aging is a degenerative process that leads to a decline in physiological functions and increases the risk of noncommunicable diseases. Obesity is particularly prevalent among individuals aged 55 to 64 years, with contributing factors including diet, physical activity, and lifestyle. This article reports the results of a community service program aimed at educating the elderly on healthy living to prevent obesity at Yayasan Pondok Lansia Bahagia Surabaya. The program was conducted on Sunday, March 10, 2024, from 08:00 to 10:30 AM at the foundation’s secretariat. Target participants included 25 elderly and pre-elderly women who regularly attend the foundation’s Islamic study groups and exercise sessions. The activities utilized counseling and practical methods, including health education and group gymnastics. Participants engaged enthusiastically, noting the material was both interesting and beneficial for their health. Evaluation through pre-test and post-test assessments demonstrated a measurable increase in participants’ knowledge after the program. This community service effectively enhanced awareness of healthy behaviors and obesity prevention among the elderly. The findings suggest that combining educational sessions with practical exercise can improve knowledge retention and encourage the application of healthy lifestyle practices. The program also highlights the importance of continuous community-based interventions in supporting elderly health and promoting sustainable habits to prevent obesity.